Design analysis and testing of flat sandwich panels under bird strike. (January 2023) - Konik, Radoslaw; Kassapoglou, Christos; Nguyen, Dean
A non-linear energy-based analytical approach to design flat sandwich panels resistant to bird strike is presented. The approach is then complemented by numerical simulation in Abaqus using smooth particle hydrodynamics to model the bird and a non-linear stress-strain model for the core material. Flat sandwich panels were designed to deform and just fail when the maximum deflections are reached for given strike energies. The panels designed with this approach were tested using gelatin birds and two different material combinations with non-toughened and toughened facesheet and core materials. The analytical and numerical approaches were found to be conservative as they predicted failure onset for the bird energies selected while the tests showed no damage. The maximum deflection and maximum strains at different locations of the panels were well predicted by the numerical analysis, but the predictions departed significantly from the tests after the first peak was reached.